Physical, Mechanical and Weathering Characteristics of Oriental beech Heat Treated with Waste Engine Oil - Caglar Altay; Davut Çiftçi; Hilmi Toker; Ergün Baysal (Drvna Industrija)
In general, vegetable oils are chosen for oil heat treatment. Oil heat treatment with waste engine oil, which is quite limited in the literature, was used in this study. After the wood material was subjected to oil heat treatment with waste motor oil, several physical parameters such as oven-dry and air-dry density, water absorption (WA) levels, and mechanical properties such as compression strength parallel to the grain (CSPG) were examined. The color changes of waste engine oil heat treated (WEOHT) specimens were examined after three months of weathering. The results showed that when oven-dry and air-dry density of WEOHT specimens increased, WA levels decreased. The WEOHT specimens had greater CSPG values than the control group. WEOHT specimens and control group revealed negative ΔL*, Δa*, and Δb* values following weathering. The WEOHT specimens had smaller total colorchanges (ΔE*) than the control group after weathering. Our results showed that higher temperature and durations resulted in lower WA, and higher air-dry density and total color changes of WEOHT specimens.